Translation Errors from Bahasa Indonesia into English - An Nissa Indira, Ruli Adha (JADEs Journal of Academia in English Education, 2022)
The purposes of this research were to find out some translation errors from Bahasa Indonesia into English and to describe the causes of translation errors. This was a descriptive qualitative research that was conducted at IAIN Langsa. The object of the research was the students of English Department, IAIN Langsa who had taken the subject of Translation III. The total number of the object was 12 students. The researchers used documentation and questionnaire as the research instruments. The documentation was taken from the result of translation exam given by the lecturer. The documentation was used to find out the translation errors made by the students. The researchers also gave a closed questionnaire that consisted of 10 questions to the students. As the result, the researchers found that there were some errors in translating texts from Bahasa Indonesia into English. The causes of errors made by the students were that the students were difficult to translate texts from Bahasa Indonesia into English; most students did not know how to differentiate between literal and idiomatic translation; most students were not familiar with translation methods; most students did not master English vocabularies well; and the students felt difficult to choose the appropriate meaning of words that have various meaning.